Application of themes from Al-Mawwaq"s work in reforming the Deoband curriculum in Islamic education in the South African Darul Ulooms - Ahmed, Shoayb (HTS teologiese studies, 2021)
Historically, most Darul Ulooms in South Africa have been modelled along the curriculum of Darul Uloom Deoband in India, which was established in 1866, and there is a need for reforming the curriculum in a world that has evolved over time. In recent years, the role of the Darul Uloom has become more crucial as more students, both nationally and internationally, are now studying at the South African Darul Ulooms. This research article aims to propose some reforms to the current Deoband curriculum adopted by some of these South African Darul Ulooms.Contribution: This proposal suggests applying themes from Al-Mawwaq’s work to foster reforms to the curriculum, which will enhance and produce scholars who are more tolerant and able to deal with the changing circumstances, both nationally and internationally.